The coal miner who became Governor - Patton, Paul E., 1937-; Suchanek, Jeffrey S., 1955- (University Press of Kentucky, 2023)
"Born in a tenant house in Fallsburg, Kentucky, Paul Patton had a humble upbringing that held few clues about his future as one of the most prominent politicians in the history of the state. From the coal mines to the governor's office, Patton's life exemplifies hard work, determination, and perseverance, as well as the consequences of personal mistakes. In The Coal Miner Who Became Governor, Patton, with Jeffrey S. Suchanek, details his personal, professional, and political life in Kentucky, starting with his career in the coal industry. After working for his father-in-law, J. C. Cooley, in the 1950s, he partnered with his brother-in-law to establish their own coal company, which they sold for millions in 1978. Patton leveraged his business connections into a political career, raising money for Democratic candidates before becoming the chair of the Kentucky Democratic Party. He first took elected office in 1981 as Pike County judge/executive; he then served a term as lieutenant governor (1991-1995), followed by an unprecedented two consecutive terms as governor. His overhaul of higher education in Kentucky led to his role as the University of Pikeville's president and chancellor, even after his political career. In this compelling account, Patton reveals the decision-making process for campaign strategies, selection of running mates, postsecondary education and workers' compensation reforms, early childhood development initiatives, and attempts at tax reform. He gives his unfiltered opinion about Mitch McConnell's "scorched-earth political philosophy" and how it has failed Kentucky, and he draws connections between public policy and party machinations during his time in office and the present day. He also addresses his fall from grace-his extramarital affair with Tina Conner and its effects on his personal and professional life"-- Provided by publisher.
Keywords: Patton, Paul E., -- 1937-; Governors -- Kentucky -- Biography.; Coal mines and mining -- Kentucky -- History -- 20th century.; Kentucky -- Politics and government -- 1951-; Pikeville (Ky.) -- Biography.; South (AL.; State & Local.; United States.; HISTORY.; State.; American Government.; POLITICAL SCIENCE.; BIOGRAPHY & AUTOBIOGRAPHY.; Politics and government; Governors; Kentucky; Biography & non-fiction prose.; Biography.; Electronic books.; autobiographies (literary genre); Biographies; Autobiographies.